2016
DOI: 10.18632/oncotarget.12487
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126 affects rheumatoid arthritis synovial fibroblast proliferation and apoptosis by targeting PIK3R2 and regulating PI3K-AKT signal pathway

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease that causes inflammation and destruction of the joints as well as an increased risk of cardiovascular disease. RA synovial fibroblasts (RASFs) are involved in the progression of RA and release pro-inflammatory cytokines. On the other hand, microRNAs (miRs) may help control the inflammatory response of immune and non-immune cells. Therefore, our study used lentiviral expression vectors to test the effects of miR-126 overexpression on RASF proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 39 publications
(35 reference statements)
3
43
0
Order By: Relevance
“…In addition, TNF‐α, IFN‐γ, IL‐17A and IL‐22 levels were elevated while IL‐10 level was lowered in miR‐126 mimic group compared with NC mimic group. Here are several possible explanations for our results: (i) according to previous studies, the overexpression of miR‐126 could promote cells' proliferation and inhibits cells' apoptosis by regulating multiple pathways; (ii) and miR‐126 also upregulates the expression of pro‐inflammatory cytokines by modulating immune‐related factors such as Dnmt1 and NF‐κB . These results in our study indicated that miR‐126 could be served as a potential treatment target in psoriasis patients.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In addition, TNF‐α, IFN‐γ, IL‐17A and IL‐22 levels were elevated while IL‐10 level was lowered in miR‐126 mimic group compared with NC mimic group. Here are several possible explanations for our results: (i) according to previous studies, the overexpression of miR‐126 could promote cells' proliferation and inhibits cells' apoptosis by regulating multiple pathways; (ii) and miR‐126 also upregulates the expression of pro‐inflammatory cytokines by modulating immune‐related factors such as Dnmt1 and NF‐κB . These results in our study indicated that miR‐126 could be served as a potential treatment target in psoriasis patients.…”
Section: Discussionsupporting
confidence: 71%
“…MiR‐126 is a member of miRNAs that are reported to be involved in the development and progression of several autoimmune diseases such as RA and SLE . A study elucidates that miR‐126 expression is increased in the CD4+ T cells of SLE patients and promotes the progression of SLE by enhancing T‐cell autoreactivity through directly targeting DNA methyltransferase 1 (Dnmt1) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[29][30][31][32] LPS increases the secretion of pro-inflammatory cytokines in fibroblast-like synoviocytes, which leads to the activation of the PI3K/ AKT and MAPK/mTOR pathways, thereby inducing apoptotic and inflammatory injury in these cells. [29][30][31][32] LPS increases the secretion of pro-inflammatory cytokines in fibroblast-like synoviocytes, which leads to the activation of the PI3K/ AKT and MAPK/mTOR pathways, thereby inducing apoptotic and inflammatory injury in these cells.…”
Section: Discussionmentioning
confidence: 99%